Parachute Design and Wind Tunnel Testing of Class 10 kg LAPAN UAV Recovery System - Herdiana, Dana; M. Ichwanul Hakim, Teuku; M. Pramutadi, Ardanto; Waryoto (Indonesian Journal of Aerospace, 2023)
LAPAN (BRIN) has already developed several types of fixed-wing UAVs that are intended to conduct civil applications. The UAV is divided by a weight class, which is 10 kg, 20 kg, and 30 kg in MTOW. In some missions, the UAV can operate in the normal way, take-off and landing by using a small runway. In some other missions, the UAV has to be launched by using a catapult and landing by net because of limited space. In the case where the UAV has to be landed between the trees, the usage of nets is not possible. Therefore the recovery system by using a parachute is designed. The cross-type parachute is designed by using analytical and simulation methods to calculate the descent velocity when the aircraft vertically lands. The descent velocity is derived from structure and payload requirements where the impact when the aircraft touches the ground will not cause damage. The designed parachute was then tested in a LAPAN Low-Speed Tunnel (LLST) to verify the design. The tests are conducted in various Reynolds numbers to observe parachute characteristics at a wide range of velocity. The wind tunnel model which is used in the test has a scale of 1:6. The Result of the simulation and the test shows that the design of the parachute was sufficient to be used as a recovery system for a class 10 kg LAPAN UAV because the descent velocity requirement is fulfilled.